Intervensi model probing promting untuk meningkatkan hasil belajar matematika siswa - Zavira, Siti; Sari, Rita; Rahayu, Nina (the Study Program of Education for Islamic Elementary School Teachers (Undergraduate), 2022)
Education directs humans to master knowledge by prioritizing appropriate and appropriate ways. In this case, the teacher plays a dominant role not only in providing material directly to students but also in order to achieve quality and quality learning success. The purpose of this study was to determine the improvement of students' mathematics learning outcomes through the probing prompting learning model. With the concept of Classroom Action Research (PTK) Kemmis and MC. Taggart, the subjects were given special treatment in math subjects. The research instruments used were observation sheets and tests. The results showed an increase in mathematics learning outcomes in fifth-grade students of MIN 1 Kota Langsa. This can be shown by the level of completeness of student learning test results classically increased from 32% (8 students) in cycle I, then in cycle II increased to 84% (21 students) by achieving an increase of up to 52%. So that the learning model can be applied to convey ordinary and decimal fraction material for class V students of MIN 1 Kota Langsa